Isu Dualisme Pemerintahan Kota Batam dan Badan Pengusahaan Batam, dalam Manajemen Tata Kelola dan Aspek Kebijakan Publik Kelembagaan - linayati lestari; Winda Roselina Effendi; Nurhayati Nurhayati; Askarmin Harun; Ronald Parlindungan Hasibuan; Dendi Sutarto; Fazarina Nurfatihah (STISIPOL Raja Haji, 2025)
Batam City is a national strategic area with the status as a Free Trade and Free Port Area (KPBPB) based on Law Number 39 Year 2009. As an implication, the management of this area is not only the responsibility of Batam City Government (Pemko Batam), but also Batam Concession Agency (BP Batam). This study aims to identify the root causes of institutional conflict between Batam City Government and Batam Concession Agency, analyze the impact of institutional politics on the effectiveness of governance and public services, present realistic and strategic policy alternatives to resolve institutional problems in Batam City, and provide recommendations based on the principles of good governanceThe method used is qualitative research with a case study approach, with secondary data sourced from books, articles, journals, documents and other literature studies.The results show that the issue of institutional dualism between the Batam City Government and the Batam Concession Agency has long been a source of institutional tension that affects the quality of governance, the effectiveness of public services, as well as public and investor confidence. Although a solution has been sought through an ex-officio mechanism, this approach has not fully resolved the root of the problem, namely overlapping authority, lack of coordination, and weak public participation. Based on an in-depth analysis of the root causes, data and trends, and consideration of the advantages and disadvantages of each option, the best recommendation is to establish a Joint Governance Body.